A REVIEW OF THE PHARMACOLOGICAL MECHANISM OF TRADITIONAL CHINESE MEDICINE IN THE INTERVENTION OF CORONARY HEART DISEASE AND STROKE - Zhang, Wenting; Gao, Kuo; Liu, Jingwei; Zhao, Huihui; Wang, Juan; Li, Yubo; Murtaza, Ghulam; Chen, Jianxin; Wang, Wei (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
In recent years, several researches have showed that Buyang Huanwu Decoction (BHD) possesses multiple target points in the intervention of diseases, and has same treatment effects on cerebrovascular diseases and cardiovascular diseases. But, there was no full report about the mechanistic and material basis in Brain-Heart concurrent treatment. The objective of the present study was to examine the pharmacological mechanism of traditional Chinese medicine in the intervention of coronary heart disease and stroke. We combined the HIT, PubChem, David Database resource and the networked pharmacology method to ultimately find out BHD’s thirty-five potential brain-heart concurrent treatment target points, and preliminarily reveal BHD’s material basis for treatment of cerebrovascular diseases and cardiovascular diseases. Finally, the study provided new information with the guidance meanings.